Optimal Power Flow Using Flower Pollination Algorithm: A Case Study of 500 kV Java-Bali Power System - Fredi Prima Sakti; Sarjiya Sarjiya; Sasongko Pramono Hadi (Department of Electrical Engineering and Information Technology,Faculty of Engineering UGM, 2017)
Flower Pollination Algorithm (FPA) is one of metaheuristic methods that is widely used in optimization problems. This method was inspired by the nature of flower pollination. In this research, FPA is applied to solve Optimal Power Flow (OPF) problems with case study of 500 kV Java-Bali power system in Indonesia. The system consists of 25 bus with 30 lines and 8 generating units. Control variables are generation of active power and voltage magnitude at PV bus and swing bus under several power system constraints. The results show that FPA method is capable of solving OPF problem. This method decreased the generator fuel cost of PT. PLN (Persero), the state-owned company in charge of providing electricity in Indonesia, up to 13.15%.